Diskriminasi Perempuan dalam Monolog Balada Sumarah Karya Tentrem Lestari - Vikrul Irsyad; Zulfadhli Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2023)
Abstract This study aims to describe: (1) forms of discrimination against women, (2) factors that cause discrimination against women, and (3) the impact of discrimination against women. This type of research is literary research with descriptive methods. The data and data sources of this research are data on discrimination against women in the Balada Sumarah monologue by Tentrem Lestari. The technique of collecting data in this research is by: (1) Reading and understanding the Balada Sumarah monologue by Tentrem Lestari; (2) Literature review, literature study related to the things being studied in order to obtain an understanding of the problem to be studied; and (3) To make an inventory of data related to discrimination against women as described in the Balada Sumarah monologue by Tentrem Lestari. The data validation technique used is the triangulation technique. After conducting various discussions in this study, it was found that forms of discrimination against women from the Balada Sumarah monologue by Tentrem Lestari include: (1) marginalization, (2) subordination, (3) stereotypes, (4) violence, and (5) workload . In addition, factors that cause discrimination are found in the monologue of Balada Sumarah by Tentrem Lestari, such as: (1) caste factors, (2) social factor, (3) economic factor. As for the impact arising from this discrimination of women: (1) such as moral burden, (2) psychologic burden, (3) destruction of idealism.